Procedurally fair provision of public projects: An axiomatic characterization - Werner Güth; Hartmut Kliemt (Friedrich Schiller University Jena and Max Planck Institute of Economics, 2011)
Unanimous voting as the fundamental procedural source of political legitimacy grants veto power to each individual. We present an axiomatic characterization of a class of bidding processes to spell out the underlying egalitarian values for collective projects of a productive state. At heart of such procedures is the determination of payments for all possible bid vectors such that equal profits according to bids emerge. Along with other intuitive requirements this characterizes procedurally fair bidding rules for advantageous projects of a collectivity.
Keywords: H4; H61; D62; D63; D71; 330; unanimity in collective decision making; Buchanan; Wicksell; Öffentliches Gut; Auktionstheorie; Gerechtigkeit; Abstimmungsregel; Public Choice; Theorie